Forecasting of YG Entertainment Stock Prices February 2022-August 2022 Using Arima Model - Novia Galuh Ramadhanty; Edwin Setiawan Nugraha (Journal of Actuarial, Finance, and Risk Management, 2022)
The stock price in investing is the main factor in determining whether an investor will invest there. With stock price prediction research, investors have an idea of whether to invest in the company. YG Entertainment is a public company in the entertainment sector with many artists and entertainment projects that have fluctuating prices. With the ARIMA (Autoregressive Integrated Moving Average) forecasting method, we can predict YG Entertainment's stock price. In this article, YG Entertainment's prediction using the ARIMA model results in a MAPE error rate of 11% with the best model being ARIMA (0,1,0). The error of the model are 33160 x103 MSE, 5758.543 RMSE, and 4366.446 MAE. This forecast will produce good output as consideration for investor who interesting buy YG Entertainment stock price